On Guaranteed Detectability for Surveillance Sensor Networks. (15th July 2012) - Zhu, Yanmin
Abstract : Surveillance is an important class of applications for wireless senor networks (WSNs), whose central task is to detect events of interest. Existing approaches seriously suffer from blind spots and low energy efficiency. In this paper, we propose a fully distributed algorithm GAP for energy-efficient event detection for surveillance applications. Employing the probabilistic approach, GAP actively tunes the active probability and minimizes the energy consumption of each sensor. The unique features of GAP are threefold. First, it provides guaranteed detectability for any event occurring in the sensing field. Second, it exposes a convenient interface of the user to specify the desired detectability. Finally, it supports differentiated service to empower better surveillance for critical spots. Without relying on costly time synchronization, GAP is a lightweight distributed protocol and is truly scalable to network scale and sensor density. Theoretical analysis and comprehensive simulation experiments are conducted, which jointly demonstrate that GAP is able to provide guaranteed detectability while significantly prolonging the system lifetime compared with other schemes.